The Trickle-Down Effect of Leaders’ Pro-social Rule Breaking: Joint Moderating Role of Empowering Leadership and Courage - Chen, Yushuai; Wang, Lan; Liu, Xin; Chen, Hong; Hu, Yunyang; Yang, Hongling (Frontiers in Psychology, 2019)
Based on social learning theory and humanistic cognitive behaviorism theory, this study examined the trickle-down effect of leader PSRB and its boundary conditions. We proposed a three-way interaction of leader PSRB, empowering leadership, and follower courage to predict follower PSRB. Data were collected from 174 leader-follower dyads. Multiple moderated regressions revealed that leader PSRB was positively related to follower PSRB, and that the effect was stronger under conditions of high empowering leadership or high courage. A three-way interaction effect suggested that the positive relationship between leader PSRB and follower PSRB was strongest when both empowering leadership and courage were high. Finally, the theoretical and practical implications were discussed.